2012
DOI: 10.1111/j.1743-6109.2011.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Among Male Patients Receiving Buprenorphine and Naltrexone Maintenance Therapy for Opioid Dependence

Abstract: Introduction Opioid-dependent men suffer from sexual dysfunctions in the short and long term. The medications used for long-term pharmacotherapy of opioid dependence also affect sexual functioning, though this has been a poorly investigated area so far. Aim To study the sexual dysfunction in opioid-dependent men receiving buprenorphine and naltrexone maintenance therapy. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 15 publications
(19 reference statements)
3
26
0
Order By: Relevance
“…Others may find buprenorphine ineffective at controlling cravings, or they cannot tolerate side effects. (Gryczynski et al, 2014; Ramdurg, Ambekar, & Lal, 2012) These results affirm existing practices of buprenorphine programs that escalate treatment intensity for patients who test positive for opiates as they are the most unstable and vulnerable. (Alford et al, 2011) Physicians and other prescribers should consider offering these patients both intensification of buprenorphine treatment (e.g., increased clinic visits, counseling, buprenorphine dosage) or facilitated transfer to a methadone program, if needed.…”
Section: 0 Discussionsupporting
confidence: 62%
“…Others may find buprenorphine ineffective at controlling cravings, or they cannot tolerate side effects. (Gryczynski et al, 2014; Ramdurg, Ambekar, & Lal, 2012) These results affirm existing practices of buprenorphine programs that escalate treatment intensity for patients who test positive for opiates as they are the most unstable and vulnerable. (Alford et al, 2011) Physicians and other prescribers should consider offering these patients both intensification of buprenorphine treatment (e.g., increased clinic visits, counseling, buprenorphine dosage) or facilitated transfer to a methadone program, if needed.…”
Section: 0 Discussionsupporting
confidence: 62%
“…Sexual dysfunctions such as erectile dysfunction (ED), ejaculatory disturbances, and lack of desire for sexual relations are often reported in a considerable number of male patients on methadone maintenance [11][12][13][14][15][16]. The exact prevalence of sexual dysfunction among this population is yet to be determined as they vary from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…The questions asked in the IIEF to assess ED were numbers 1, 2, 3, 4, 5 and 15. This IIEF-1 scale is scored as no ED (score[26][27][28][29][30], mild(22)(23)(24)(25), mild to moderate(17)(18)(19)(20)(21), moderate(11)(12)(13)(14)(15)(16), or severe (0-10). The higher the score the lower the ED.…”
mentioning
confidence: 99%
“…To increase the complexity of the interpretation of existing data in this field, a high prevalence of common dysfunctions, such as premature ejaculation, erectile dysfunction and reduced desire, have been reported in heroin-dependent patients during opioid receptor antagonists treatment with naltrexone [16] , once again challenging the simplistic view of a direct pharmacological influence of the opioid system on the sexual response. Accordingly, another research group found that sexual functioning does not improve when drug use is stopped [17] , further suggesting the possibility of factors other than the pharmacological effects of drugs contributing to sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%